The Role of School Management in Emergency Reconstruction and Recovery: Evidence from Secondary Schools in Northwest Cameroon - Genevarius Nji (Ilmu Inovasi Nusantara, 2026)
Education systems in crisis-affected regions face profound disruptions that threaten the accessibility, quality, and sustainability of learning, as observed in Cameroon's Northwest Region, which has experienced prolonged emergencies. One of the critical problems in this context is the limited capacity of education management to effectively coordinate reconstruction and recovery efforts during and after emergencies. Weak managerial preparedness, inadequate resources, and insufficient policy support have constrained schools' ability to respond adaptively to crises. This study aims to examine the role of education management in emergency reconstruction and recovery processes and to identify the managerial challenges that hinder effective education delivery during emergencies in Cameroon. The study employed a descriptive survey research design. Data were collected using a structured questionnaire administered to 215 teachers and 85 school administrators in the northwest region of Cameroon. Simple random sampling was used to select teachers, while purposive sampling was applied to select school administrators with direct managerial responsibilities. Data were analyzed using descriptive statistical techniques to capture trends and patterns in respondents’ perceptions and experiences. The findings reveal that many school administrators lack essential skills in emergency preparedness, crisis response, and post-emergency recovery management. Furthermore, the study identified key obstacles, including inadequate funding, weak institutional planning, limited professional training, and insufficient government support. However, these challenges can be managed if strategic planning, sustainable funding mechanisms, and strong institutional commitment are strengthened. The study implies that strengthening education management capacity is crucial for effective emergency response and long-term recovery. It recommends targeted capacity-building programs, increased government investment, and the integration of emergency management frameworks into educational policy to ensure resilient and inclusive education systems in crisis-prone contexts